2018
DOI: 10.1002/lsm.22797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐frequency near‐infrared diode laser irradiation on periodontal tissues during experimental tooth movement in rats

Abstract: This study demonstrates that high-frequency near-infrared diode laser irradiation of periodontal tissue leads to metabolic activation, which ultimately increases the rate of tooth movement. Lasers Surg. Med. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…High-frequency near-infrared diode laser irradiation enhanced the proliferation and migration of human gingival epithelial cells [41] and mouse calvarial osteoblasts [42]; promoted epithelialization and bone formation in tooth extraction sockets, possibly by activating cell proliferation and differentiation in vivo [43]; and reduced temporomandibular joint pain [44,45]. Moreover, high-frequency near-infrared diode laser irradiation of periodontal tissue leads to metabolic activation, thereby increasing the tooth movement rate in rats [46]. Thus, high-frequency near-infrared diode laser irradiation may affect chondrocyte metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…High-frequency near-infrared diode laser irradiation enhanced the proliferation and migration of human gingival epithelial cells [41] and mouse calvarial osteoblasts [42]; promoted epithelialization and bone formation in tooth extraction sockets, possibly by activating cell proliferation and differentiation in vivo [43]; and reduced temporomandibular joint pain [44,45]. Moreover, high-frequency near-infrared diode laser irradiation of periodontal tissue leads to metabolic activation, thereby increasing the tooth movement rate in rats [46]. Thus, high-frequency near-infrared diode laser irradiation may affect chondrocyte metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The calcium pool would be triggered when the NIR acts on the ER, and ERK1/2 would then be activated. The phosphorylated ERK1/2 can transport into cell nucleus and interact with different kinds of transcription factors (such as AP1, ATF, EIK‐1, and NF‐kB), which finally promotes cell proliferation and migration on wound bed …”
Section: Resultsmentioning
confidence: 99%
“…Tooth movement during orthodontic therapy is usually associated with bone resorption on the pressure side and bone regeneration on the tension side 129 . Several strategies have been proposed to decrease the treatment time in orthodontic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Gunji et al . 129 examined the effect of high frequency NIR diode laser irradiation with a wavelength of 910 nm on tooth movement. They reported that 910 nm NIR laser irradiation on periodontal tissue resulted in metabolic activation, which ultimately enhanced tooth movement during orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%